Kelly Akashi - formations - Dickens, Lauren Schell; Katrib, Ruba 1982-; Nguyen, Julien 1990-; Sorkin, Jenni 1977- (Inventory Press, 2023)
"As the first in-depth monograph on the artist, Kelly Akashi: Formations accompanies the major survey exhibition organized by the San José Museum of Art and traveling nationally. Much like the artist's own work, the catalogue cultivates relationships between objects and materials to investigate how they can actively convey their histories and potential for change. Spanning nearly ten years of her practice, the publication follows the artist from graduate school to more recent research into the inherited impact of Japanese Americans' incarceration during World War II. Akashi's works in glass, cast bronze, multipart installations, and photographic contact prints are given further context through scholarly essays by San José Museum of Art's senior curator Lauren Schell Dickens, curator Ruba Katrib, and art historian Dr. Jenni Sorkin, as well as a conversation between Akashi and painter Julien Nguyen. Dickens provides an overview of some of the themes in Akashi's work as they spiral through each other: studies of weeds, fossils, and rocks expand to consider time, ancestry and inheritance, botanical and geologic memory, and kinship between beings. Sorkin examines Akashi's practice within a larger context of skilled craft, what she terms "geoaesthetics," and vernacular culture in California. Katrib looks at the centrality of the artist's hands and body in her practice. Along with extensive plates and installation photography, the book features a new photography project by Akashi, a record of her scavenging for history in the site of her family's imprisonment in a WWII Japanese American incarceration camp. Exhibition: San José Museum of Art, San José, USA (03.09.2022-21.05.2023)."
Seite [200]: "Published on the occasion of the exhibition Kelly Akashi: Formations organized by the San José Museum of Art: San José Museum of Art, September 3, 2022-May 21, 2023; Frye Art Museum, Seattle, June 17-September 3, 2023; Museum of Contemporary Art San Diego, September 21, 2023-February 18, 2024".- Includes bibliographic references
Keywords: Akashi, Kelly -- 1983-; Akashi, Kelly / 1983- / Exhibitions; Japanese American artists / Exhibitions; Exhibition catalogs; Ausstellungskatalog -- San José Museum of Art -- 03.09.2022-21.05.2023 -- San José, Calif.; Ausstellungskatalog -- Charles and Emma Frye Art Museum -- 17.06.2023-03.09.2023 -- Seattle, Wash.; Ausstellungskatalog -- Museum of Contemporary Art San Diego -- 21.09.2023-18.02.2024 -- San Diego, Calif.; Bildband